Malaysia towards zero poverty by 2020 - Elhadary, Yasin; Samat, Narimah (2015)
Since 1970, Malaysia have been adopted various policies to reduce poverty and address the socio-spatial inequality. These policies managed to reduce poverty rate from 52.4% in 1970 to 1.7 % in 2012. However, inequalities and disparity among regions and ethnic groups have not been properly addressed. Policies that worked well nationally might not be suitable to be used in addressing poverty at local level. Thus, this paper aims to critically look at the strengths and weaknesses of such policies particularly in eliminating poverty. The paper is based heavily on the review of the recent literature and the data gathered from Economic Planning Unit-EPU and the Department of Statistics, Malaysia. Empirical experiences have shown that Malaysia has managed to reduce poverty beyond the declaration of MDG; halving poverty by 2015. However several issues need to be addressed as the country aim to be a developed nation with zero poverty as indicated in its vision 2020. Although the slogan "growth with equity" was used, spatial disparities were found among region such as between Sabah and Penang. Penang State, which has experienced steady economic growth, has implemented top-up model of eliminating poverty where families earned less than poverty income line received top-up income from the state government since 2013, claimed to have zero poverty rate. However, the sustainability of this approach is questionable. In addition to that, the sign of incidence of poverty between rural and urban and among ethnic minorities is quite clear. This inequality with external factors (illegal migration and global economy) poses some challenges for achieving the vision 2020. By evaluating the policies and analyzing regional disparities the paper will enrich the literature on poverty and help the planners to formulate sound poverty eradication polices.